2008
DOI: 10.1128/aem.00692-07
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Fungal Flora in Indoor Dust by Ribosomal DNA Sequence Analysis, Quantitative PCR, and Culture

Abstract: In recent years increasing attention has been given to the potential health effects of fungal exposure in indoor environments. We used large-scale sequencing of the fungal internal transcribed spacer region (ITS) of nuclear ribosomal DNA to describe the mycoflora of two office buildings over the four seasons. DNA sequencing was complemented by cultivation, ergosterol determination, and quantitative PCR analyses. Sequences of 1,339 clones were clustered into 394 nonredundant fungal operational taxonomical units… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
171
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 188 publications
(188 citation statements)
references
References 75 publications
16
171
0
Order By: Relevance
“…In Mexico City, Penicillium is also the second most common genus 15 . However, in studies performed in other countries, such as France, the USA, Chile and Cuba, Cladosporium has stood out as the most prevalent genus [16][17][18] .…”
Section: Discussionmentioning
confidence: 99%
“…In Mexico City, Penicillium is also the second most common genus 15 . However, in studies performed in other countries, such as France, the USA, Chile and Cuba, Cladosporium has stood out as the most prevalent genus [16][17][18] .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, HTS was rated superior over cultivation, given its ability to detect more obligate, slow growing and rare fungi (Al-Sadi et al 2015, Oono et al 2015. Whereas the general lack of congruence between mycobiomes generated by cultivation and HTS can be safely postulated nowadays (Pitkaranta et al 2008), much less is known about environmental correlations of these differing data sets.…”
Section: Introductionmentioning
confidence: 99%
“…Using qPCR has provided valuable information on the occurrence of the most common indoor fungi and this method shows great promise for the rapid provision of quantitative data on the occurrence of the studied organisms [82]. However, apart from cloning and sequencing of amplified fungal DNA, or in some cases DGGE followed by sequencing, these methods do not produce detailed information on previously unknown or unexpected taxa [24]. A comparison of methods has suggested that the cloning, cultivation and qPCR methods complement each other, generating a more comprehensive picture of fungal flora than any of the methods used alone [24].…”
Section: Fungal Pathogenicity and Mycotoxigenicity In Highrisk Groupsmentioning
confidence: 99%
“…These can include EI and long-term sampling, e.g. of settled dust or pumped air, and use of total fungal analyses, such as for ergosterol, beta 1-3 glucan or total molds by the CAMERANEA method [21][22][23] or fungal DNA analysis via quantitative or qualitative polymerase chain reaction (PCR) [21][22][23][24].…”
Section: Targeted and Proportionate Approaches For Identifying And Momentioning
confidence: 99%
See 1 more Smart Citation